A Simple Approach to Measuring the Share of Early Childbirths Likely Due to Child Marriage in Developing Countries - Wodon, Quentin (Taylor and Francis, 2020)
Child marriage has large negative effects on the girls who marry early and their children, as well as communities and societies as a whole. Ending child marriage is a target under the Sustainable Development Goals, but investments to delay the age at first marriage remain limited in countries where child marriage is widespread. As part of a broader argument to make the economic case for ending child marriage, this paper provides a simple approach for measuring the share of early childbirths likely due to child marriage in developing countries. This estimation matters because many of the negative impacts of child marriage on development outcomes for the girls who marry early and their children are through early childbirths – having a child before the age of 18 (for a mother), or being born of a mother younger than 18 (for a child). The estimates provided in this paper suggest that most early childbirths in developing countries are likely due to child marriage.